2012
DOI: 10.1051/0004-6361/201117168
|View full text |Cite
|
Sign up to set email alerts
|

The scaling relation between the mass of supermassive black holes and the kinetic energy of random motions of the host galaxies

Abstract: Context. Thanks to the improved angular resolution of modern telescopes and kinematic models, the existence of supermassive black holes (SMBHs) in the inner part of galaxies, regardless their morphology and nuclear activity, has been established on quite solid grounds. A possible correlation between the mass of SMBHs (M • ) and the evolutionary state of their host galaxies is expected and is currently under a heated debate. Aims. Based on the recent 2D decomposition of 3.6 μm Spitzer/IRAC images of local late-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 57 publications
2
22
1
Order By: Relevance
“…It is also evident that we obtain very similar results using the LYNMIX_ERR routine and using the least squares (LS − TEST) without considering errors in both variables. Different is the behavior obtained by FITEXY that gives always higher slopes, as it has already been shown in our previous works (Feoli & Mancini 2009;Mancini & Feoli 2012). It means that the routine FITEXY is more sensible to the estimation of errors with respect to LYNMIX_ERR.…”
Section: Resultsmentioning
confidence: 46%
See 3 more Smart Citations
“…It is also evident that we obtain very similar results using the LYNMIX_ERR routine and using the least squares (LS − TEST) without considering errors in both variables. Different is the behavior obtained by FITEXY that gives always higher slopes, as it has already been shown in our previous works (Feoli & Mancini 2009;Mancini & Feoli 2012). It means that the routine FITEXY is more sensible to the estimation of errors with respect to LYNMIX_ERR.…”
Section: Resultsmentioning
confidence: 46%
“…However, the aim of this paper is not to discover what the best among all the correlations is, but only to emphasize that a not widely − used relation such as the M • − M b σ 2 e , is at least as tight as the most famous ones and that in many cases, as for example in Mancini & Feoli (2012), it can offer better predictions than the others. To this aim we have used our relation to infer the masses of the SMBHs in the center of the two giant galaxies NGC 3842 and NGC 4889 that, following McConnell et al (2011), show "experimental values significantly higher than the ones predicted by the standard M • −σ e and M • − L laws".…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The continuous stream of multiwavelength experimental data and the use of modern methods to analyze them, is now giving more and more convincing evidence that these SMBHs are strongly correlated to the characteristics of their parent galaxy (Magorrian, Tremaine & Richstone 1998;Tremaine et al 2002;Marconi & Hunt 2003;Gebhardt et al 2003;Häring & Rix 2004;Feoli & Mele 2005;Aller & Richstone 2007;Graham 2008aGraham , 2008bHu 2008;Kisaka, Kojima & Otani 2008;Feoli & Mancini 2009;Gültekin 2009a;Beifiori 2009Beifiori , 2011Mancini & Feoli 2012) and, on the other hand, affect the processes of galaxy formation and evolution (Silk & Rees 1998;Burkert & Silk 2001;Cavaliere & Vittorini 2002;King 2003;Wyithe & Loeb 2003;Haiman, Ciotti, & Ostriker 2004;Granato et al 2004;Sazonov et al 2005;Murray, Quataert & Thompson 2005;Begelman & Nath 2005;Hopkins et al 2006a;Croton et al 2006;Sijacki et al 2007;Pipino 2009aPipino , 2009b. In a more cosmological context, numerical simulations and semi-analytical models revealed that the environment, in which these galaxies reside, may heavily influence the growth and the activity of the SMBHs (Di Matteo, Springel & Hernquist 2005;Hopkins et al 2006b;Hopkins et al 2008;Ciotti, Ostriker ...…”
Section: Introductionmentioning
confidence: 99%